Nanoparticle-Protein Corona Interactions in Biological Milieu: Differential Toxicity Profiles in Prostate Cancer and Normal Cell Lines - mahya karbalaee; Zahra Sadeghi; Mohammad Vahid Ahmadianpour; Babak Jahangiri; Reza Valipour; Seyed Ahmad Aleyasin; Jamshid Raheb (Journal of Sciences, Islamic Republic of Iran)
Prostate cancer stands as the second most prevalent cancer among men globally and represents a significant cause of mortality in Iran. Notably, nanotechnology has emerged as a valuable tool in the realm of medical research, offering advancements in both cancer diagnosis and treatment. Prior research has shown that nanoparticles, when entering biological environments like plasma or serum, are surrounded by a layer of proteins referred to as the protein corona. The protein coronas' composition differs across various disorders, affecting the kind and amount of proteins that attach to the nanoparticle surface. This study aimed to assess the toxicity of protein coronas loaded onto various nanoparticles, including gold, graphene, and superparamagnetic iron oxide nanoparticles (SPIONs), in prostate cancer and normal cell lines. Plasma samples from cancer patients and healthy individuals were procured, and nanoparticles (gold, SPIONs, graphene oxide) were synthesized, with their charge and size verified using zeta method. Subsequently, the MTT assay was used to study the toxicity of combinations of nanoparticles (gold, SPIONs, graphene oxide) and their associated protein coronas on the LNCaP prostate cancer cell line and healthy HFF fibroblast cells. Gold nanoparticles exhibited higher toxicity towards cancer cells compared to the other two nanoparticles. Conversely, SPIONs and graphene oxide did not manifest significant toxicity on healthy cells. The increased toxicity of graphene oxide-associated protein coronas highlights the complex relationship between nanoparticle composition and protein corona properties, offering important insights for targeted cancer therapy techniquesthe quantisation of aromatic amines simultaneously in fairly complex matrix of dyes effluents and biological samples (human serum) by simple GC-FID with adequate sensitivity.